2020
DOI: 10.1111/1751-2980.12847
|View full text |Cite
|
Sign up to set email alerts
|

Second‐look endoscopy‐guided therapy under sedation prevents early rebleeding after variceal ligation for acute variceal bleeding

Abstract: Objectives To investigate whether second‐look endoscopy (SLE)‐guided therapy could be used to prevent post‐endoscopic variceal ligation (EVL) early bleeding. Methods Consecutive cirrhotic patients with large esophageal varices (EV) receiving successful EVL for acute variceal bleeding (AVB) or secondary prophylaxis were enrolled. The patients were randomized into a SLE group and a non‐SLE group (NSLE) 10 days after EVL. Additional endoscopic interventions as well as proton pump inhibitors and octreotide adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Eighteen studies were included in the systematic review (Figure 1) of which 14 were retrospective observational studies, 5,7,8,11–19,21,22 four studies were prospective, with two prospective observational studies 4,20 and two randomized controlled trials 23,24 . The main study characteristics are provided in Table S5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen studies were included in the systematic review (Figure 1) of which 14 were retrospective observational studies, 5,7,8,11–19,21,22 four studies were prospective, with two prospective observational studies 4,20 and two randomized controlled trials 23,24 . The main study characteristics are provided in Table S5.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the treatment in case of acute PBUB, most studies used the vasoactive drug therapy used for variceal bleeding (somatostatin, octreotide or terlipressin) as well as intravenous PPI. More variability exists across the studies regarding the endoscopic type of treatment applied, with Re‐EBL being used to treat PBUB in eight studies 5,12,14–16,19,23,24 . Other types of endoscopic therapies were used as well (argon plasma coagulation, oesophageal variceal obliteration, like sclerotherapy and cyanoacrylate injection, epinephrine injection, hemoclip).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that hypoxia and shock were more common in the maximal EVL group than in the minimal EVL group, the minimal EVL strategy may be chosen for patients with variceal bleeding with poor general conditions or hemodynamic instability. Although the effects of second-look endoscopic treatment were not analyzed during this study, Wang et al 23 recently reported that second-look endoscopic treatment, which is performed after EVL for acute bleeding of large endoscopic varices, is an option for reducing early rebleeding.…”
Section: Discussionmentioning
confidence: 99%